A wide distribution of Beiji nairoviruses and related viruses in Ixodes ticks in Japan - Kishimoto, Mai; Itakura, Yukari; Tabata, Koshiro; Komagome, Rika; Yamaguchi, Hiroki; Ogasawara, Kohei; Nakao, Ryo; Qiu, Yongjin; Sato, Kozue; Kawabata, Hiroki; Kajihara, Masahiro; Monma, Naota; et al. (Ticks and tick-borne diseases, 2024)
Beiji nairovirus (BJNV), in the family Nairoviridae, the order Bunyavirales, was recently reported as a causative agent of an emerging tick-borne zoonotic infection in China. This study investigated the prevalence of BJNV in ticks in Japan. Screening of over 2,000 ticks from multiple regions revealed a widespread distribution of BJNV and BJNV-related viruses in Japan, particularly in the northern island, and in other high altitude areas with exclusive occurrence of Ixodes ticks. Phylogenetic analysis identified three distinct groups of nairoviruses in ticks in Japan: BJNV, Yichun nairovirus (YCNV) and a newly identified Mikuni nairovirus (MKNV). BJNV and YCNV variants identified in ticks in Japan exhibited high nucleotide sequence identities to those in China and Russia with evidence of non-monophyletic evolution among BJNVs, suggesting multiple cross-border transmission events of BJNV between the Eurasian continent and Japan. Whole genome sequencing of BJNV and MKNV revealed a unique GA-rich region in the S segment, the significance of which remains to be determined. In conclusion, the present study has shown a wide distribution and diversity of BJNV-related nairoviruses in Ixodes ticks in Japan and has identified unique genomic structures. The findings demonstrate the significance of BJNV as well as related viruses in Japan and highlight the necessity of monitoring emerging nairovirus infections and their potential risks to public health.